PSYCHOLOGICAL AND PEDAGOGICAL CHARACTERISTICS OF PERSONALITY FORMATION OF ACADEMIC LYCEUM STUDENTS (Conferencea, 2023)
This article discusses the analysis of the main directions of formation and development of the field of informatics education in academic lyceums. Based on pedagogical data, the author studied and analyzed specific aspects of the analysis of the main directions of the formation and development of the field of informatics education in academic lyceums on the basis of existing scientific literature.